2016
DOI: 10.3233/jad-150807
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Alzheimer’s Disease and Schizophrenia Dataset Revealed Different Expression Pattern in Learning and Memory

Abstract: Alzheimer's disease (AD) and schizophrenia (SZ) are both accompanied by impaired learning and memory functions. This study aims to explore the expression profiles of learning or memory genes between AD and SZ. We downloaded 10 AD and 10 SZ datasets from GEO-NCBI for integrated analysis. These datasets were processed using RMA algorithm and a global renormalization for all studies. Then Empirical Bayes algorithm was used to find the differentially expressed genes between patients and controls. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Next, we calculated the average expression value of multiple probe IDs that matched to an official gene symbol and took this value to represent the expression intensity of the corresponding gene symbol. The renormalization method and scripts are described in our previous publications [39, 40]. The distributions of RMA processed and global renormalized gene expression values across all studies are shown in Supplementary Figure 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we calculated the average expression value of multiple probe IDs that matched to an official gene symbol and took this value to represent the expression intensity of the corresponding gene symbol. The renormalization method and scripts are described in our previous publications [39, 40]. The distributions of RMA processed and global renormalized gene expression values across all studies are shown in Supplementary Figure 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we calculated the average expression value of multiple probe IDs that matched to an official gene symbol, and took this value to represent the expression intensity of the corresponding gene symbol. The renormalization method was reported in our previous publication ( Li et al, 2016 ). The distributions of RMA processed and global renormalized gene expression values in two studies were showed in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…There is a decline in the number of interneurons, particularly nNOS-expressing interneurons, with aging 78,79 , and the removal of their tonic vasodilatory signal could cause decreases in cerebral blood flow that are thought to contribute to dementia 25 . Indeed, alterations of nNOS and TAC1 (encoding the precursor to Substance P) expression have been implicated in Alzheimer's disease 80,81 . Protecting these blood-flow controlling neurons from insults and damage could be a promising strategy for preventing neurovascular disorders.…”
Section: Discussionmentioning
confidence: 99%